2008
DOI: 10.1159/000134904
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Characteristics and Health Perceptions among Male and Female Visitors to CAM Practitioners in a Total Population Study

Abstract: Background: The aim was to explore the prevalence of visitors to CAM practitioners in a total population with reference to sex, self-rated health status and socio-demographic characteristics. Methods: The paper reports findings from the Nord-Trøndelag Health Study (HUNT 2), a total population-based health survey of 42,277 respondents conducted in central Norway who answered questions on visits to a CAM practitioner. Variables included were age, marital status, education, receiving social welfare benefits, life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
5
8
1
Order By: Relevance
“…The observed prevalence of 8.7% visiting a CAM practitioner in YH2 (2001) is similar to that for adults in the same population (9.4%) [14]. It was higher than the 2.0% visiting a CAM practitioner in USA in a 1996 study [5], but lower than the 23% visiting practitioners in San Diego, USA in 2001 [15].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The observed prevalence of 8.7% visiting a CAM practitioner in YH2 (2001) is similar to that for adults in the same population (9.4%) [14]. It was higher than the 2.0% visiting a CAM practitioner in USA in a 1996 study [5], but lower than the 23% visiting practitioners in San Diego, USA in 2001 [15].…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, although it is known from cross sectional surveys that CAM practitioners are visited by people with chronic conditions [21], socio demographic variables usually play an equally important role [14]. This is evident in this study, where none of the chronic diseases mentioned were associated with current CAM visits, but having experienced musculoskeletal pain or chronic disease (migraine, use of asthma medicines and other diseases lasting longer than three months) predicted future CAM visits.…”
Section: Discussionmentioning
confidence: 58%
“…However, as those who have experienced better health also do the same, it is difficult to make an assumption about possible causal relationships. Nevertheless, self-rated global health, which has been found to be more strongly associated with seeing CAM practitioners than sociodemographic variables in Norway, 14 is an important factor. It reflects many aspects of health and lifestyle in addition to simply the purely physical 21 -aspects identified elsewhere as important to those using CAM.…”
Section: Summary Of Resultsmentioning
confidence: 94%
“…Furthermore, although the question mentioned several types of CAM practitioners, an even more comprehensive list would likely have increased the prevalence since it would enhance the respondents recall. The urban population was underrepresented in this study and a non-responder analysis of the 1997 data [18] found that older people were more likely not to answer the CAM question than younger people. Nevertheless, the age distribution was similar to other studies [6,19-21].…”
Section: Discussionmentioning
confidence: 99%